Disparate Rates of Cesarean Delivery in Term Nulliparous Women with Hypertensive Disorders of Pregnancy - Penfield, Christina A.; Nageotte, Michael P.; Wing, Deborah A. (American Journal of Perinatology, 2019)
Objective To evaluate the prevalence of cesarean delivery in women with hypertensive disorders of pregnancy (HDP), and explore whether maternal, sociodemographic, or obstetric comorbidities contribute to cesarean delivery rates.Study Design This is a retrospective cohort study of nulliparous, term, singleton, vertex women using the 2013 U.S. National Vital Statistics Report. We compared prevalence of risk factors for cesarean delivery between women with and without HDP, and then calculated probabilities of cesarean delivery after controlling for these risk factors.Results In this cohort of 1,439,977 women, the unadjusted probability of cesarean delivery in women with HDP was 39.5 versus 26.8% in those without the diagnosis (p < 0.01). Hypertensive women had more risk factors for cesarean delivery, most notably morbid obesity (9.0 vs. 3.1%, p < 0.01), diabetes (9.9 vs. 4.4%, p < 0.01), and induction of labor (59.2 vs. 26.9%, p < 0.01). Despite this, after controlling for these risk factors, hypertensive women remained significantly more likely to undergo cesarean delivery (35.1 vs. 26.4%, p < 0.01).Conclusion Even after controlling for multiple comorbidities, hypertension remained a significant risk factor for cesarean delivery in nulliparous women at term. Hypertensive women may therefore represent an important target population in efforts aimed at reduction of cesarean rates.
Keywords: hypertensive disorders of pregnancy; cesarean delivery; perinatal; preeclampsia